2019
DOI: 10.31580/apss.v4i2.642
|View full text |Cite
|
Sign up to set email alerts
|

Generation Y Employees in the Ict Sector. The Influence of Emotional Intelligence, Spiritual Intelligence and Perceived Organizational Support Towards Intention to Stay.

Abstract: The aim of this research is to examine the influence of emotional and spiritual intelligence on the intention to stay by Gen Y employees in the ICT sector in Malaysia. The mediating effect of perceived organizational support (POS) among the independent variables and dependent variable wil be tested. Primarly, this research would fulfill three requirements. Firstly, how the perception of emtional intelligence would influence Gen Y to remain with an organization. Secondly, the extent to which spiritual intellige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The results show that teaching personnel have a relatively high level of job satisfaction influenced by spiritual leadership, this is due to the establishment of good communication and relationships between coworkers, followed by interest in the work they do, and satisfaction with the support given to them by their superiors. Job satisfaction is not the sole variable that influences the intention to stay of teaching personnel (Mohsin et al, 2021;Valeau et al, 2021;Weeratunga, 2019), but differences can be seen between individuals who have satisfaction and those who do not. This study found that job satisfaction plays a major role in increasing intention to stay.…”
Section: Resultsmentioning
confidence: 99%
“…The results show that teaching personnel have a relatively high level of job satisfaction influenced by spiritual leadership, this is due to the establishment of good communication and relationships between coworkers, followed by interest in the work they do, and satisfaction with the support given to them by their superiors. Job satisfaction is not the sole variable that influences the intention to stay of teaching personnel (Mohsin et al, 2021;Valeau et al, 2021;Weeratunga, 2019), but differences can be seen between individuals who have satisfaction and those who do not. This study found that job satisfaction plays a major role in increasing intention to stay.…”
Section: Resultsmentioning
confidence: 99%